2000
DOI: 10.1046/j.1365-2494.2000.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the response in intake of silage and animal performance after wilting of grass before ensiling: a review

Abstract: This review examines the response in intake of silage and animal performance after wilting of grass before ensiling. It uses data from eighty‐five published comparisons. Initial analysis identified those variables having the greatest influence on the increase in dry‐matter (DM) intake of grass silage owing to wilting. Total water loss, drying rate of the wilted material and ammonia‐N concentration of the unwilted material were the variables most closely and positively correlated to the proportional increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
12

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 33 publications
1
47
0
12
Order By: Relevance
“…Silveira et al (1980) e Narciso Sobrinho et al (1998 verificaram melhora significativa no consumo de MS da silagem de capim-elefante em resposta ao emurchecimento. Wright et al (2000) revisaram 85 trabalhos sobre os fatores que afetam o consumo e o desempenho de animais alimentados com silagem de capim produzida com forragem emurchecida e concluíram que a perda total de água, a velocidade de perda de água da forragem emurchecida, as características da forragem (como teores de PB e N-NH 3 ) e a digestibilidade da MS da silagem proveniente da forragem não-emurchecida são as variáveis mais exatas e positivamente correlacionadas ao aumento do consumo de MS, como resultado do emurchecimento.…”
Section: Resultsunclassified
“…Silveira et al (1980) e Narciso Sobrinho et al (1998 verificaram melhora significativa no consumo de MS da silagem de capim-elefante em resposta ao emurchecimento. Wright et al (2000) revisaram 85 trabalhos sobre os fatores que afetam o consumo e o desempenho de animais alimentados com silagem de capim produzida com forragem emurchecida e concluíram que a perda total de água, a velocidade de perda de água da forragem emurchecida, as características da forragem (como teores de PB e N-NH 3 ) e a digestibilidade da MS da silagem proveniente da forragem não-emurchecida são as variáveis mais exatas e positivamente correlacionadas ao aumento do consumo de MS, como resultado do emurchecimento.…”
Section: Resultsunclassified
“…Van Os et al (1995) demonstrated a signifi cant DMI reduction and a trend for decreased milk production in cows fed grass silages with 13 vs 6% ammonia-N. In their study, rumen ammonia was higher in cows fed silage with 13% ammonia-N. Dry matter intake dropped 0.3 Kg/d when ammonia-N in grass silage fed to dairy cows increased from 7 to 20% (Wright et al 2000). The analysis of 47 experiments indicated that high concentrations of ammonia-N in grass silage fed to dairy cows had a negative eff ect on DMI, milk production and milk composition (Huhtanen et al, 2003).…”
Section: Introductionmentioning
confidence: 84%
“…Huhtanen, 1994;Offer et al, 1998;Steen et al, 1998;Wright et al, 2000). These studies have used comparisons between direct-cut v. slightly or heavily wilted silages and direct-cut silage v. field-or barn-dried hay harvested at the same stage of grass maturity.…”
Section: Silage Fermentation Characteristicsmentioning
confidence: 99%
“…Generally the DM intake of wilted silages have exceeded that of directcut silages the magnitude of wilting response being affected by the fermentation quality of direct-cut silage, type of additive used and weather conditions during the wilting period. Most likely a significant part of the wilting response in these studies on SDMI is related to changes in the extent and type of fermentation owing to lower water activity in wilted silages, especially when direct-cut silages are preserved without additives (Yan et al, 1996;Wright et al, 2000). To avoid this problem, we used a statistical model to account for separate effects of silage fermentation quality and DM concentration in the present evaluation.…”
Section: Silage Fermentation Characteristicsmentioning
confidence: 99%